Using visualization strategy to improve strategic reading among ESL students - Loh, Pack Swan @ Esther (2008)
This study attempts to investigate whether visualization strategy (VS) is effective in improving the reading comprehension performance of two classes of Form 2 (N = 90) students in reading expository texts in English. It also attempts to provide an insight into the perceptions of the students towards the use of visualization strategy. The study employed a mixed-method approach, combining both quantitative and qualitative approaches focusing on an urban secondary school in the district of Luyang, Kota Kinabalu, Sabah. Two English language classes, namely Form 2D (experimental group) which comprises 41 students and, Form 2E (control group) which comprises3 9 students, participated in the study. The experimental group was provided with a series of reading sessions using visualization strategy (as a treatment) on top of the normal teaching and learning process, while the control group was only taught using the normal teaching and learning process. Quantitative data was collected via the pre and post tests and was analyzed using the Statistical Package for Social Sciences (SPSS) version 15.00. Qualitative data, obtained through semi structured interviews and reflective journals, were content analysed to derive relevant themes. The key findings from the pre- and post-tests showed that the students responded positively to the use of visualization strategy in their reading tasks. Findings derived from the semi-structured interviews and reflective journals revealed that students have positive perceptions towards the use of visualization strategy in reading expository texts. In overall terms, the findings seem to indicate the feasibility of using visualization strategy as a tool to improve the reading comprehension process of reading expository texts.